2021
DOI: 10.1177/02666669211027206
|View full text |Cite
|
Sign up to set email alerts
|

Understanding consumers’ purchase intention towards online paid courses

Abstract: With the unprecedented development of information and communication technologies, online learning is increasingly seen as an important channel for knowledge acquisition. Although knowledge payment platforms have attracted a considerable number of consumers, little is known about the determinants of purchase intention of online learning consumers for online paid courses (OPCs). In this study, we identify the mechanism underlying online learning consumers’ purchase intentions towards online paid courses (OPCs) b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 94 publications
0
4
0
Order By: Relevance
“…(3) In this paper, we found a positive correlation between perceived irreplaceability and the purchase intention for online health popular science information. Previous studies have proposed perceived irreplaceability and analyzed the drivers of perceived irreplaceability, i.e., proposing that perceived enjoyment and perceived usefulness are positively correlated with perceived irreplaceability [ 55 , 70 ]. There are also studies that have found a positive impact of perceived irreplaceability on the acceptance of medical wearables [ 78 ], whereas it is currently unknown what effect perceived irreplaceability as an antecedent variable will have on intention to purchase online health popular science information.…”
Section: Discussionmentioning
confidence: 99%
“…(3) In this paper, we found a positive correlation between perceived irreplaceability and the purchase intention for online health popular science information. Previous studies have proposed perceived irreplaceability and analyzed the drivers of perceived irreplaceability, i.e., proposing that perceived enjoyment and perceived usefulness are positively correlated with perceived irreplaceability [ 55 , 70 ]. There are also studies that have found a positive impact of perceived irreplaceability on the acceptance of medical wearables [ 78 ], whereas it is currently unknown what effect perceived irreplaceability as an antecedent variable will have on intention to purchase online health popular science information.…”
Section: Discussionmentioning
confidence: 99%
“…This experience is influential in shaping their performance expectations and trust towards the Online Paid Courses (OPCs), significantly impacting their purchase intentions. Positive personal trial experiences can lead to a higher perception of course quality and increased trust in the platform, thus enhancing the likelihood of purchase [8].…”
Section: Personal Trial Experiencementioning
confidence: 99%
“…Paid MOOCs are introduced to guarantee MOOC platforms' sustainable development (Baker and Passmore, 2016). However, the reported low purchase rate (Shah, 2021a) or repurchase rate (Hone and El Said, 2016) discloses the struggles that many platforms experience in cultivating education consumers' loyalty (Chen et al, 2021). Thus, understanding determinants that induce MOOC consumers' favorable actions (i.e.…”
Section: Literature Review 21 Paid Moocs and The Quality Factorsmentioning
confidence: 99%
“…Expectedly, a growing body of research examining the monetization of MOOCs has been observed (Veletsianos and Shepherdson, 2016;Ma et al, 2022). As shown in Table 1, past studies suggest that MOOC consumers' behavioral intentions are primarily affected by three quality dimensions (Ma et al, 2022): course content quality(CCQ) (Albelbisi, 2020), platform quality(PQ) (Zhou et al, 2022), and instructor quality(IQ) (Chen et al, 2021). However, these three quality dimensions are often used in the isolation (Zhou et al, 2022).…”
Section: Literature Review 21 Paid Moocs and The Quality Factorsmentioning
confidence: 99%
See 1 more Smart Citation